2004
DOI: 10.1016/j.neuroimage.2004.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cortical change in Alzheimer's disease, brain development, and schizophrenia

Abstract: This paper describes algorithms that can identify patterns of brain structure and function associated with Alzheimer's disease, schizophrenia, normal aging, and abnormal brain development based on imaging data collected in large human populations. Extraordinary information can be discovered with these techniques: dynamic brain maps reveal how the brain grows in childhood, how it changes in disease, and how it responds to medication. Genetic brain maps can reveal genetic influences on brain structure, shedding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
321
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 360 publications
(331 citation statements)
references
References 98 publications
9
321
0
1
Order By: Relevance
“…The typical curvilinear trajectories of thickness changes with age share strikingly similar temporal and regional similarities with the progression of synaptic pruning as observed postmortem, confirming the potential of cortical thickness to reliably identify the brains critical development periods (Sowell et al, 2003;Gogtay et al, 2004;Shaw et al, 2006aShaw et al, , 2008Thompson et al, 2004). Moreover, cortical thickness studies have an exquisite resolution, allowing for the identification of local alterations with high precision.…”
supporting
confidence: 58%
“…The typical curvilinear trajectories of thickness changes with age share strikingly similar temporal and regional similarities with the progression of synaptic pruning as observed postmortem, confirming the potential of cortical thickness to reliably identify the brains critical development periods (Sowell et al, 2003;Gogtay et al, 2004;Shaw et al, 2006aShaw et al, , 2008Thompson et al, 2004). Moreover, cortical thickness studies have an exquisite resolution, allowing for the identification of local alterations with high precision.…”
supporting
confidence: 58%
“…Maps of cortical thickness were created exactly as in ref. 6. All 40 individual brain volumes were rigidly reoriented into the standardized coordinate system of the ICBM-53 average brain, correcting for head tilt and alignment differences between subjects but leaving scale differences intact.…”
Section: Methodsmentioning
confidence: 99%
“…Cortical thickness was computed from 3D brain MRI scans as the 3D distance between the inner and outer surfaces of the cortical gray matter. This measure of cortical integrity is sensitive to subtle disease-related changes and correlates with cognitive decline in Alzheimer's disease and schizophrenia (6).…”
mentioning
confidence: 99%
“…To date, our research group has reported correlations for the MMSE, a global measure of cognitive function, 5,76 for a verbal fluency test and a picture naming test (animal fluency and Boston Naming test), 77 and for delayed recall of verbal information (California Verbal Learning Test). 78 Strong associations between MMSE and cortical atrophy were seen in the entorhinal, parahippocampal, precuneus, superior parietal, and subgenual cingulate/orbitofrontal cortices.…”
Section: Fig 5 This Longitudinal 3d Mri Studymentioning
confidence: 99%